Drivers of Boycott Intention and Loyalty: Evidence from McDonald’s Indonesia - Laksmita Chandra; Ratna Roostika (Islamic Studies and Development Center in Collaboration With Students' Research Center Universitas Negeri Padang, 2026)
This study examines the influence of consumer ethnocentrism, social media exposure, and perceived efficacy on boycott intention toward McDonald’s Indonesia, as well as its implications for consumer boycott loyalty. The research is motivated by the intensifying boycott movements in Indonesia following the issuance of the Indonesian Ulema Council (MUI) Fatwa No. 83 of 2023, which prohibits support for Israeli aggression. A quantitative approach was employed through an online survey of 251 active social media users exposed to boycott-related discourse. Data were analyzed using SmartPLS with the PLS-SEM method. The results reveal that consumer ethnocentrism, social media influence, and perceived efficacy significantly and positively affect boycott intention. Furthermore, boycott intention exerts a positive impact on consumer boycott loyalty. These findings highlight the critical role of national values, digital media dynamics, and collective efficacy in shaping consumer participation in boycott movements, while also reinforcing loyalty to boycott actions against McDonald’s Indonesia. The study contributes to the literature on consumer behavior and activism by demonstrating how socio-cultural and digital factors interact to strengthen boycott-driven loyalty.